(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Smoking marijuana and 9- tetrahydrocannabinol (THC) (dronabinol, Marinol) is used for treating anorexia and weight loss caused by the human immunodeficiency virus-1 (HTV-1). However, there have been concerns that these chemicals may have a negative influence on the immune systems of HTV-infected persons. The writer has conducted randomised, potential, controlled trial in adults who have HIV-infection and who have been receiving protease inhibitor-that contains high active antiretroviral therapy to assess the usage of marijuana cigarette (3.95 percent THC), dronabinol (2.5 mg), and an oral placebo in adults who have HIV-infection receiving protease inhibitor-containing highly active antiretroviral therapy (HAART). Immunological presentation (flow cytometric quantification of cellular subpopulations, B cells, and natural killer [NK] cells) and immunological function (induced cytokine production, NK cell activity, and lymphoproliferation) tests were carried out at the beginning and on a regular basis.